A study of woodpecker's pecking process and the impact response of its brain. (October 2017) - Liu, YuZhe; Qiu, XinMing; Ma, HongLei; Fu, WenWen; Yu, T.X.
Highlights: The woodpecker pecking process is recorded and the pecking force is measured by force sensor. The effect of neck during the impact is confirmed to be negligible. Using Material Point Method, the pecking process is simulated and validated by experiment. The brain injury criteria for woodpeckers are proposed and compared with simulation results. Abstract: Head impact injuries always cause severe diseases and deaths of human. In contrast, the woodpeckers are able to withstand fierce impact during pecking without brain damage. Several studies have reported about the mechanisms how woodpecker protects its brain, but the experimental result of the pecking impulse with the corresponding pecking process are still lacking. In this study, a trunk-like piezoelectric force sensor was used to measure the pecking impulse, and the corresponding pecking process was recorded by a high speed camera. Based on the results, there is negligible effect on the neck during the impact. After experiment, the woodpecker head was scanned by micro-Computed Tomography (micro-CT) and the pecking process was simulated by Material Point Method (MPM). The simulated impact impulse matches well with the experimental result. Using the simulation results, the energy transmission and the impact responses of the brain are discussed. Head Injury Criterion (HIC) and Average Resultant Acceleration (Ar) for woodpecker are proposed by scaling analyses to measure the possibilities of brain damage. Finally, the impact response under higher pecking velocities is analyzed using numerical simulation and the influence of the rhamphotheca layer in the beak is discussed.